HUKUM KEPAILITAN DAN PERMASALAHANNYA DI INDONESIA - Niru Anita Sinaga; Nunuk Sulisrudatin (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2016)
The monetary crisis that occurred in Indonesia in mid-1997 has given unfavorable influence on the national economy, causing great hardship on the business community in resolving the debts to continue their activities, and impacts are detrimental to society. At that time a lot of the problems that arise. Many companies have trouble paying its debt obligations to creditors and further many companies into bankruptcy (Bankruptcy). Terperosoknya rupiah, has raised at least 3 (three) negatively affect the national economy, namely: Negative balance of payments, spread Negative, Negative equity. The above conditions resulted in an amount of companies that threatened bankruptcy for the national economy and the inability to pay debts of companies that is generally done in the form of dollars. To solve this problem we need a legislation governing debt, it is fast, effective, efficient and fair. However, in practice these laws still causes a lot of problems. For that we need a solution to overcome, so what is the purpose of making bankruptcy law itself can be achieved, namely justice for the parties